Auf die Tour!: Jüdinnen und Juden in Singspielhalle, Varieté und Kabarett - Habsburgermonarchie bis Amerika - Korbel, Susanne (2020)
In the monography Auf die Tour, I analyze the participation of Jews in popular culture in Vienna, Budapest and New York. I argue that entertainment in vaudevilles was shaped between the perception of difference and similarity, between human trafficking, covert prostitution, anti-Semitism and nationalism. Ultimately, my research shows how a space for Jewish-non-Jewish people was created in the coinciding of the mass migration movement and the emerging mass culture between the Habsburg Monarchy and the United States.